Wetting and interfacial behavior of Fe-based self-fluxing alloy-refractory compound systems - Umanskyi, O.P.; Umanskyi, O.P.; Storozhenko, M.S.; Krasovskyy, V.P. (Сверхтвердые материалы, 2017)
In this study the wettability and interfacial behaviour of the TiC–FeNiCrBSiC and TiB₂–FeNiCrBSiC systems were investigated. The wetting experiments were performed by the sessile drop method at 1150 °C under a vacuum. The contact angles of TiC and TiB₂ wetting by melted Fe-based self-fluxing alloy were 51° and 36°, respectively. Thermodynamic calculations were carried out to understand the metal-ceramic interaction mechanism in the TiC–FeNiCrBSiC and TiB₂–FeNiCrBSiC systems. The structure of the interface region in the TiB₂–FeNiCrBSiC system was characterized by the optical microscopy and SEM-EDS analysis. The formation of Fe, Ni, Cr and Mo complex borides was revealed within the interface region of the TiB₂–FeNiCrBSiC system.